Sweden - Phillips, Charles, 1962- (Washington, D.C. : National Geographic, 2009)
A basic overview of the history, natural environment, geography, culture, government, and economy of Sweden; and includes photographs, maps, a glossary, a bibliography, a list of resources, an index, and a time line.
Map on endpapers.
Includes bibliographical references (p. 61) and index.
8.5
5-8
Keywords: Sweden -- Juvenile literature; Sweden; Sweden